Enhancement of plasticizer adsorption by utilizing a rice bran-derived adsorbent - Chih-Ming Ma (Elsevier, 2021)
Bis(2-ethylhexyl) phthalate (DEHP) and di-n-butyl phthalate (DBP) are commonly used plasticizers in many countries and are detected at significant levels in the environment. Wastewater treatment plants are currently unable to completely treat wastewater discharges containing plasticizers. Rice bran was used to prepare magnetic-activated biochar (MAB) as a reusable adsorbent for enhanced adsorption of DEHP and DBP. The influence of the adsorbent dose, temperature, and adsorption time on the removal efficiency of MAB was studied using response surface methodology (RSM). An analysis of the results indicated that the optimum conditions were a MAB dose of 3.6 g/L, a temperature of 49 °C, and an adsorption time of 454 min for DEHP removal; and a MAB dose of 3.7 g/L, a temperature of 36 °C and an adsorption time of 312 min for DBP removal. The adsorption isotherm data were well fitted by the Langmuir isotherm model, and the adsorption kinetic data were reasonably described by the pseudosecond-order model. MAB is a potential adsorbent for DEHP and DBP removal because of good removal efficiency and reusability.